VLSI implementation of multicarrier complementary coded CDMA downlink system. (2020) - Raj, A. Albert; Latha, T.
Abstract: In recent years, many studies on the development of CDMA have been conducted in industries and academic Institutions. Multicarrier complementary coded code division Multiple Access (MC CC-CDMA) is being largely used for high-speed data transmission .However the main limitation of such a system is Multi carrier Interference (MAI). The use of parallel Interference cancellation (PIC) gives an excellent solution to suppress MAI. In this article the author present the analytical testing and investigation of the MC CC-CDMA system using different schemes. The use of PIC in frequency-selective decomposition channels is also analyzed here. Simulations in Matlab are carried out on flat vanishing and bidirectional frequency selective disappearing channels and are used to verify theoretical analysis. The result shows that, error rate of MC CC-CDMA with PIC is much lower than without PIC. The author also presents an FPGA Implementation of the downlink system and achieved the power reduction with reduced complexity circuit.